Plastic Versus Self-Expanding Metallic Stents for the Management of Malignant Hilar Biliary Strictures - Azar, Riad R. (2011)
Palliation of jaundice as primary or adjunctive therapy has become the standard approach to patients with unresectable malignant obstruction of the biliary hilum. However, use of plastic or self-expanding metallic stents (SEMS) as preferred management remains controversial. Information on rates of complications are needed before optimal management can be determined.